The morphology of insular shelves as a key for understanding the geological evolution of volcanic islands: Insights from Terceira Island (Azores). (22nd May 2014) - Quartau, R.; Hipólito, A.; Romagnoli, C.; Casalbore, D.; Madeira, J.; Tempera, F.; Roque, C.; Chiocci, F. L.
Abstract Shelves from volcanic ocean islands result from the competition between two main processes, wave erosion that forms and enlarges them and volcanic progradation that reduces their dimension. In places where erosion dominates over volcanism, shelf width can be used as a proxy for the relative age of the subaerial volcanic edifices and reconstruction of their extents prior to erosion can be achieved. In this study, new multibeam bathymetry and high‐resolution seismic reflection profiles are exploited to characterize the morphology of the insular shelves adjacent to each volcanic edifice of Terceira Island in order to improve the understanding of its evolution. Subaerial morphological and geological/stratigraphic data were also used to establish the connection between the onshore and offshore evolution. Shelf width contiguous to each main volcanic edifice is consistent with the known subaerial geological history of the island; most of the older edifices have wider shelves than younger ones. The shelf edge proved to be a very useful indicator in revealing the original extent of each volcanic edifice in plan view. Its depth was also used to reconstruct vertical movements, showing that older edifices like Serra do Cume‐Ribeirinha, Guilherme Moniz, and Pico Alto have subsided while more recent ones have not. The morphology of the shelf (namely the absence/presence of fresh lava flow morphologies and several types of erosional, depositional, and tectonic features) integrated with the analysis of the coastline morphology allowed us to better constrain previous geological interpretations of the island evolution.